2020
DOI: 10.1007/s00592-019-01469-5
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the risk of gestational diabetes mellitus based on the 2013 WHO criteria: a prediction model based on clinical and biochemical variables in early pregnancy

Abstract: AcknowledgementsThis investigator-initiated study was funded by the Belgian National Lottery, the Fund of Academic studies of UZ Leuven and the Fund Yvonne and Jacques François -de Meurs of the King Boudewijn Foundation. The sponsors of the study had no role in the design of the study; or in the collection, handling, analysis; or interpretation of the data; or in the decision to write and submit the manuscript for publication KB and RD are the recipient of a 'Fundamenteel Klinisch Navorserschap Fonds Wetenscha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 33 publications
3
38
0
Order By: Relevance
“…Most models showed moderate discrimination, with AUCs mostly above 0.70, which is consistent with previous findings [21,22,24,29]. Previous studies have investigated models derived from electronic health records for the predictions of GDM in machine learning models or conventional logistic regressions, but these studies included fewer participants than ours, did not compare the two methods, involved limited variables, or did not comprehensively estimate the performance of discriminations and calibrations [18,21,22,24,29]. The current studies extend these previous studies by validating predictive ratio cutoff points of 0.3 and 0.7 originating from general maternal characteristics and biochemical data by comparing the performance of machine learning and traditional logistic regression models for the prediction of GDM.…”
Section: Comparisons Andsupporting
confidence: 89%
See 1 more Smart Citation
“…Most models showed moderate discrimination, with AUCs mostly above 0.70, which is consistent with previous findings [21,22,24,29]. Previous studies have investigated models derived from electronic health records for the predictions of GDM in machine learning models or conventional logistic regressions, but these studies included fewer participants than ours, did not compare the two methods, involved limited variables, or did not comprehensively estimate the performance of discriminations and calibrations [18,21,22,24,29]. The current studies extend these previous studies by validating predictive ratio cutoff points of 0.3 and 0.7 originating from general maternal characteristics and biochemical data by comparing the performance of machine learning and traditional logistic regression models for the prediction of GDM.…”
Section: Comparisons Andsupporting
confidence: 89%
“…Recent prediction models for GDM have been developed using conventional regression analyses [17][18][19]. However, machine learning, a data analysis technique that develops algorithms to predict outcomes by "learning" from data, is increasingly emphasized as a competitive alternative to regression analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, elevated triglycerides at early gestation may be regarded as a potential biomarker for prediabetic disorders that will lead to hyperglycemia when pregnancy progresses and the physiologic environment changes. Although the establishment of early risk assessment tools is challenging due to the heterogeneity of the disease [25], a recent study by Benhalima et al found that the inclusion of biomarkers such as triglycerides improves the accuracy of risk assessment models to predict the risk for the development of GDM at the start of pregnancy, as also underlined by the data of our study [26]. Of note, we observed no association between cholesterol (LDL, HDL or total cholesterol) with GDM development.…”
Section: Discussionsupporting
confidence: 75%
“…Advancing age [ 6 , 7 ], a family history of diabetes [ 7 ], and ethnicity of a non-Anglo-European decent [ 8 ] are well-established risk factors for GDM. Multiparity is also associated with an increased risk of GDM [ 6 ], although advancing maternal age and weight gain both during and between pregnancies seem to mediate the effect [ 9 ].…”
Section: Introductionmentioning
confidence: 99%